IMPROVING EMPLOYEE PERFORMANCE THROUGH KEPEMIMPINAN, ORGANIZATIONAL CULTURE AND COMPETENCE: A STUDY AT THE OFFICE OF THE KESBANGPOL PATI AGENCY - Tri Handayani; Suhana (SEAN Institute, 2022)
Thisresearch aims to analyze the influence of leadership, organizational culture and competence on the Performance of Pati Regency Kesbangpol Employees. The population of this study was all 58 employees. While the number of samples is equal to the number of populations. So this study used a saturated sampling technique, where the entire population was used as a sample. Kuesioner is used as the main data collection tool.. Data analysis in this study used multiple linear regression. The results showed that leadership variables do not affect employee performance, organizational culture variables have a positive effect on employee performance and competency variables have an effect positive to employee performance. This research has both theoretical and practical implications.